2013
DOI: 10.1016/j.alcohol.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal ethanol exposure results in dose-dependent impairments in the acquisition and timing of the conditioned eyeblink response and altered cerebellar interpositus nucleus and hippocampal CA1 unit activity in adult rats

Abstract: Exposure to ethanol in neonatal rats results in reduced neuronal numbers in the cerebellar cortex and deep nuclei of juvenile and adult animals. This reduction in cell numbers is correlated with impaired delay eyeblink conditioning (EBC), a simple motor learning task in which a neutral conditioned stimulus (CS; tone) is repeatedly paired with a co-terminating unconditioned stimulus (US; periorbital shock). Across training, cell populations in the interpositus (IP) nucleus model the temporal form of the eyeblin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 88 publications
(128 reference statements)
0
13
0
Order By: Relevance
“…Interestingly, other in vitro electrophysiology experiments showed that alcohol exposure led to relatively greater inhibitory inputs to the Purkinje cells in the vermis ( 40 ). In the cerebellar deep nuclei, activity in the interpositus nucleus of the cerebellum was diminished and did not develop as rapidly in neonatal alcohol-exposed rats relative to controls during EBC ( 41 , 42 ).…”
Section: Laboratory Animal Workmentioning
confidence: 87%
“…Interestingly, other in vitro electrophysiology experiments showed that alcohol exposure led to relatively greater inhibitory inputs to the Purkinje cells in the vermis ( 40 ). In the cerebellar deep nuclei, activity in the interpositus nucleus of the cerebellum was diminished and did not develop as rapidly in neonatal alcohol-exposed rats relative to controls during EBC ( 41 , 42 ).…”
Section: Laboratory Animal Workmentioning
confidence: 87%
“…Data indicates that disruption of memory by ethanol is due to its effect on attention, sensory-motor function, emotion or motivation that impairs the efficiency of learning and encoding [ 231 ]. Ethanol might induce destructions of hippocampus-dependent learning and memory [ 232 , 233 ] and impair of the cholinergic neuronal system [ 234 ] by oxidative stress via the generation of ROS and lipid peroxidation [ 235 ]. Ethanol-induces presynaptic dysfunction in dorsal hippocampal glutamatergic neurons and thereby causes deficits in spatial memory [ 19 ].…”
Section: Toxin-induced Experimental Models Of Memory Impairmentmentioning
confidence: 99%
“…This includes significant loss of pyramidal neurons in CA1 and CA3 and granule neurons in the dentate gyrus (Ieraci & Herrera, 2007; Ikonomidou et al, 2000; Klintsova et al, 2007; Livy, Miller, Maier, & West, 2003; Tran & Kelly, 2003; Uban et al, 2010). Developmental ethanol exposure also produces neuroanatomical and electrophysiological defects in hippocampal circuitry (Diaz et al, 2014; Everett, Licon-Munoz, & Valenzuela, 2012; Lindquist, Sokoloff, Milner, & Steinmetz, 2013; Sakata-Haga et al, 2003). Defects in the hippocampus correlate with behavioral deficits, particularly with learning and memory (Banuelos et al, 2012; El Shawa et al, 2013; Hamilton et al, 2010; Idrus, McGough, Riley, & Thomas, 2014; Kelly, Pierce, & West, 1987; Thomas, Idrus, Monk, & Dominguez, 2010; Wagner, Zhou, & Goodlett, 2014; West, Kelly, & Pierce, 1987; Zink et al, 2011).…”
Section: Fasd Neuropathology In Animal Modelsmentioning
confidence: 99%